Rancang Bangun Pengering Buah Pinang Otomatis Menggunakan Pendekatan Quality Function Deployment (QFD) - Tri Wahyudi; Ratih Rahmahwati; Silvia Uslianti (OPSI, 2022)
The processing of dried betel nut by the people of West Kalimantan consists of 2 stages, namely drying and stripping the betel nut. The drying process usually carried out by farmers is drying directly in the sun, and the smoking process uses fire to heat. The method of drying the areca nuts takes about 14-15 days. This study will examine the problems faced by farmers in the process of drying areca nuts. Based on the issue of drying areca nuts, it is necessary to have an alternative method of drying that is more efficient. Areca nut drying machine is an alternative to obtain dried betel nut relatively quickly with well-maintained fruit quality. The design of the areca nut drying machine is made based on the identification of farmers' needs. Identifying farmers' needs or desires will be an attribute of product development, and technical parameters are determined to meet these product attributes. The method that will be used is the Quality Function Deployment (QFD) method. The study results that priority attributes must be completed based on calculations in the planning matrix using QFD. The design of the areca nut has dimensions of 260 mm x 490 mm, with the specifications of the tool consisting of two main parts, namely an inner filter (a place for betel nuts) and a betel nut dryer.